Pengaruh Layanan M-Banking, Religiusitas, dan Pengetahuan Perbankan Syariah Terhadap Preferensi Menabung Masyarakat Di Bank Syariah - Dian Fajar Suryani; Mustapa Khamal Rokan; Nur Ahmadi Bi Rahmani (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This study aims to identify the effect of m-banking services, religiosity and knowledge of Islamic banking on the savings preferences of the people of Aceh Singkil at Bank Syariah Indonesia. This study uses primary data. The research method used is quantitative with data processing techniques multiple linear regression analysis, taking research samples with Simple Random Sampling as many as 102 respondents which are disseminated through questionnaires using an intermediary google form. The results of data processing on the coefficient of determination test (R2) is 0.697 or 69.7%. While the t test shows that the m-banking service variable (X1) has no significant effect on saving preferences with a negative t count -2.455 <t table 1.660 with a Sig. 0.016 <0.05. The religiosity variable (X2) has significant influence on saving preferences with t count 4.676 <1.660 with a Sig. 0.000 < 0.05. Islamic banking knowledge variable (X3) has significant and significant effect on saving preferences with t count 7.414 > 1.660 with a value of Sig. 0.000 < 0.05. The results of the data processing prove that simultaneously (test f) the three independent variables tested simultaneously have a positive effect on the dependent variable. This research has a positive impact on the tendency of people to determine their preferences for saving at Indonesian Sharia Banks in the Aceh Singkil district, meaning that it opens opportunities for banks to increase product/service introduction to the public.